Exploration and exploitation in complex search tasks: How feedback influences whether and where human agents search - Billinger, Stephan; Srikanth, Kannan; Stieglitz, Nils; Schumacher, Terry R. (Strategic Management Journal, 2021)
Research Abstract Exploration and exploitation in strategic decision‐making entails decisions about whether and where to search for new alternatives to improve the status quo. Prior research has not explored how decisions about whether to continue search (vs. stop search or satisfice) and where to search (near vs. far) are interrelated. We report laboratory experiment results on how individuals decide whether and where to search in a complex, combinatorial task. We find that different feedback variables influence the decision to stop search from decisions regarding how broadly to search. Our results suggest that not accounting for the decision to continue (or stop) searching, separately from breadth of search, can lead to incorrect predictions regarding how feedback influences search behavior. Managerial Abstract Managers concerned about the performance of their company face two challenges—they have to find out what potential performance is feasible given their business environment and which organizational policies to implement to realize it. We use a stylized laboratory experiment to better understand how feedback from experimentation informs such a learning process. We find that early‐stage feedback has a lasting impact on performance aspirations and managerial expectations about feasible performance. Superior early feedback thereby motivates more sustained experimentation with organizational policies. In contrast, more recent feedback guides the extent to which managers are willing to engage in more radical policy adjustments, especially in the latter stages of a learning process.